Estimating Fluctuations in Oil and Gas Investment - Roy Endré Dahl; Petter Osmundsen (Center for Economic Studies and ifo Institute (CESifo), 2014)
Governments in extraction countries are anxious to estimate expected investment in development projects, since they represent an essential element of the macro economy. The overall level of activity is also crucial to oil companies, since the macro picture affects cost levels, the supplies market and recruitment opportunities. The paper outlines factors that explain fluctuations in investment in petroleum projects on the Norwegian continental shelf.
Keywords: M21; L71; F21; E32; 330; investments; oil industry; cost overruns; megaprojects; business cycles